Comparative analysis of Da Vinci robotic surgery and laparoscopic surgery for congenital choledochal cyst in neonates - Xilin Liao; Zebing Zheng; Huijuan Wang; Yu Liao; Qing Du; Lu Huang; Chengyan Tang; Yuan Gong; Zeping Li; Daiwei Zhu; Yuanmei Liu; Zhu Jin (BMC Pediatrics)
Abstract Objective This study aims to compare and analyze the clinical efficacy and safety of Da Vinci robotic surgery (RS) versus traditional laparoscopic surgery (LS) for the treatment of congenital choledochal cyst (CCC) in neonates. Methods We retrospectively analyzed sixty-seven neonatal cases of CCC admitted to our hospital between December 2018 and December 2024. The cases were categorized into the robotic group (n = 32) and the laparoscopic group (n = 35) based on the surgical technique employed. We systematically compared baseline data, intraoperative metrics, and postoperative recovery between the two groups, focusing on total operative time, biliary-intestinal anastomosis time, and postoperative recovery outcomes. Results The two groups were comparable regarding baseline characteristics such as age, gender, weight, and cyst diameter (P > 0.05), with no significant differences in preoperative general conditions (P > 0.05); The total operative time was longer for RS compared to LS (208.54 ± 10.43 min vs. 194.54 ± 17.21 min, P = 0.016). However, the time required for biliary-intestinal anastomosis was shorter in RS (38.25 ± 9.78 min vs. 52.40 ± 9.83 min, P < 0.001), and intraoperative bleeding was significantly lower (P < 0.05); Postoperative abdominal drainage was significantly reduced in RS, with a shorter duration for drainage tube removal, demonstrating a statistically significant difference (P < 0.05). There was no statistically significant difference in the overall complication rate between the two groups. Conclusion Da Vinci robotic-assisted surgery is safe and feasible for the treatment of neonatal CCC. RS offers advantages such as a shorter biliary-intestinal anastomosis time, reduced tissue trauma, and faster recovery, warranting its promotion in neonatal surgical practices. Trial registration Retrospectively registered.